Comparison of Computed Tomography Perfusion and Multiphase Computed Tomography Angiogram in Predicting Clinical Outcomes in Endovascular Thrombectomy. Issue 9 (24th June 2022) - Tan, Zefeng; Parsons, Mark; Bivard, Andrew; Sharma, Gagan; Mitchell, Peter; Dowling, Richard; Bush, Steven; Churilov, Leonid; Xu, Anding; Yan, Bernard
Abstract : Background: In patients with acute stroke who undergo endovascular thrombectomy, the relative prognostic power of computed tomography perfusion (CTP) parameters compared with multiphase CT angiogram (mCTA) is unknown. We aimed to compare the predictive accuracy of mCTA and CTP parameters on clinical outcomes. Methods: We included patients with acute ischemic stroke who had anterior circulation large vessel occlusion within 24 hours of onset in Melbourne Brain Centre at the Royal Melbourne Hospital. All patients underwent CTP for endovascular thrombectomy, and the mCTA collateral score was determined using CTP-reconstructed mCTA images. The primary outcome was 90-day functional outcomes defined by modified Rankin Scale. Multivariable logistic regression models analyzed associations between mCTA and CTP parameters and 90-day functional outcomes. The ability to discriminate 90 days-functional outcomes was compared between mCTA collateral score and CTP parameters using receiver operating curve analysis and C statistics. Results: One hundred and twenty patients were included. The median age was 69 years (interquartile range, 60–79), the median baseline National Institutes of Health Stroke Scale score was 14 (interquartile range, 9–19). The baseline ischemic core volume, defined by CTP-based relative cerebral blood flow <30%, was associated with excellent functional outcome (modified Rankin Scale score 0–1; odds ratio, 0.942 [−0.897 to −0.989]; P =0.015) and poor functional outcome (modified Rankin Scale score 5–6; odds ratio, 1.032 [1.007–1.056]; P =0.010) at 90 days in the analysis of multivariable regression. There was no significant association between the mCTA score and excellent functional outcome ( P =0.58) or poor functional outcome ( P =0.155). The relative cerebral blood flow <30%-based regression model best fit the data for the 90-day poor functional outcome (C statistic, 0.834). Conclusions: The CTP-based ischemic core volume may provide better discrimination for 90-day functional outcomes for patients with acute stroke undergoing endovascular thrombectomy than the mCTA collateral score.